Utilization of Complementary and Alternative Therapies in Youth with Developmental Disabilities - Tenenbaum, Rachel (Evid Based Complement Alternat Med, 2019)
Oxidative stress is understood to be involved in the ontology and maintenance of different developmental disabilities. Some complementary and alternative medicine (CAM) therapies have been proposed to modify this relationship by affecting oxidative stress pathways. However, it is unclear which of these CAM therapies are used among children with different developmental disabilities. This study examines the use of these therapies among 10,218 children between the ages of 4 and 17 using the 2012 Child Complementary and Alternative Medicine (CAM) Supplement of the National Health Interview Survey (NHIS) to highlight a potential avenue for intervention and prevention efforts. The results suggest that children with developmental disabilities are more likely to utilize particular CAM therapies that may alter oxidative stress pathways. Future work is needed to assess the potential moderating effect of these CAM therapies and oxidative stress levels among children with different developmental disabilities.